Clinical and demographic profile Volkmann's ischemic contracture presenting in Tigray (Ethiopia) - Cugola, Landino; Fasolo, Giampaolo (Acta Biomedica Atenei Parmensis, 2022)
Objective: Volkmann's ischemic contracture (VIC) represents the outcome of a compartment syndrome, not adeguately managed during the acute phase. It is still to be found in the developing contries, while it is rarely present in the developed countries. In this report we refer on our african experiences on VIC, because we beleive might be useful for last generation of italian orthopaedics which rarely have a chance to see Volkmann's cases. Matherials and Methods: AA report their 2-years experience of 16 patients aged 7 to 17, presenting various entities of Volkmann's in Tigrai. Results: in all patients there has been an aceptable recovery of hand function, also although the difficulty to verify the outcomes because of the scarce overlapping of the clinical status and different operations. Conclusions: attention shall be drawn to the outcomes and a healthcare education is necessary in those villages where cures are entrusted to the so called "traditional doctors" who are nothing more than "bone-setters".